2006
DOI: 10.1007/11775331_15
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Congruence Between Organizational Structure and Task Performance: A Simulation Approach

Abstract: Abstract. Reorganization of the structure of an organization is a crucial issue in multi-agent systems that operate in an open, dynamic environment. Ideally, autonomous agents must be able to evaluate and decide the most appropriate organization given the environment conditions. That is, there is a need for dynamic reorganization of coordination structures. In this paper, we describe how simulation studies could help to determine whether and how reorganization should take place, and present a simulation scenar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Elsewhere in other publications we have discussed how these different functions are synthesized to create the whole (PMFserv) [12,20,28,32] . Dignum et al suggested several intriguing ideas for doing this, but so far have not completed that implementation [33] . Likewise, it also describes the way in which archetypical follower agents autonomously decide things like emotional activations, social mobilization, group membership, and motivational congruence with a given leader or group.…”
Section: Simulating State and Substate Actors With Countrysimmentioning
confidence: 99%
“…Elsewhere in other publications we have discussed how these different functions are synthesized to create the whole (PMFserv) [12,20,28,32] . Dignum et al suggested several intriguing ideas for doing this, but so far have not completed that implementation [33] . Likewise, it also describes the way in which archetypical follower agents autonomously decide things like emotional activations, social mobilization, group membership, and motivational congruence with a given leader or group.…”
Section: Simulating State and Substate Actors With Countrysimmentioning
confidence: 99%
“…Our current research on the development of a simulation tool for reorganization experimentation aims at the identification of conditions and requirements for change, ways to dynamically incorporate changes in systems, how to determine when and what change is needed, and how to communicate about changes. In (Dignum et al, 2006) we presented a simulation scenario, VILLA, to evaluate different reorganization forms and understand triggers for reorganization.We are currently working on a simulation that analyzes the relation between agent capabilities and organizational structure, when the objective is to share knowledge on a particular task.…”
Section: Agent Organization Simulationmentioning
confidence: 99%
“…Many researchers have devoted their efforts to empirical studies and simulation experiments to ascertain such relationships, e.g. Dalton (1980) summarizes the literature addressing the empirical evidence between organization structure and performance [3], Dignum (2005) assumes that reorganization of the structure of an organization is a crucial issue to enhance task performance in an open and dynamic environment [4], Csaszar (2012) develops and tests a model of how organizational structure influences organizational performance using evidence from mutual funds [5].…”
Section: Introductionmentioning
confidence: 99%